DESIGN OF A SPACE FRAME CHASSIS FOR UTEM PERODUA ECO-CHALLENGE CAR - Ashari, Muhamad Hafizullah; Mansor, Muhd Ridzuan; Mohd Tahir, Musthafah; Hassan, Muhammad Zahir; Mohd Adrinata, Shaharuzaman (2011)
This paper presents the design of a space frame chassis for UTeM Perodua Eco Challenge car. Several concept designs were generated for the chassis and the final design selected was modeled in 3D using CATIA V5 CAD software during the design stage in the project. Low carbon steel ASTM A36 was selected as the space frame material due to high strength, low cost and versatility with many manufacturing processes. The chassis structural strength was later analyzed using finite element analysis in bending and torsion load cases. Results from the structural analyses showed that the chassis is able to perform safely as per design requirement.